2005
DOI: 10.1111/j.1528-1167.2005.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Changes and Disease‐modifying Effects of Scopolamine in the Pilocarpine Model of Epilepsy in Rats

Abstract: Summary: Purpose:We describe the use of a clinically relevant pharmacological intervention that alters the clinical history of status epilepticus (SE)-induced spontaneous recurrent seizures (SRS) in the pilocarpine model and the possible plastic changes underlying such an effect.Methods: Two hours after pilocarpine-induced SE (320-350 mg/kg, i.p.), rats received scopolamine 1-2 mg/kg i.p. or saline, every 6 h for 3 days. After that, osmotic minipumps were implanted for continuous delivery of scopolamine or sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Research from our group has provided evidence that anticholinergic agents might provide an effective means to modify disease progression in the pilocarpine model of epilepsy ( 89 , 90 ). The administration of scopolamine starting 3 h after the onset of pilocarpine-induced SE was effective in altering epileptogenesis ( 90 ).…”
Section: Antiepileptic Drugs (Aeds)mentioning
confidence: 99%
See 1 more Smart Citation
“…Research from our group has provided evidence that anticholinergic agents might provide an effective means to modify disease progression in the pilocarpine model of epilepsy ( 89 , 90 ). The administration of scopolamine starting 3 h after the onset of pilocarpine-induced SE was effective in altering epileptogenesis ( 90 ).…”
Section: Antiepileptic Drugs (Aeds)mentioning
confidence: 99%
“…Research from our group has provided evidence that anticholinergic agents might provide an effective means to modify disease progression in the pilocarpine model of epilepsy ( 89 , 90 ). The administration of scopolamine starting 3 h after the onset of pilocarpine-induced SE was effective in altering epileptogenesis ( 90 ). Similarly, in a more extensive study, the administration of biperiden (another cholinergic antagonist) was also shown to be effective in altering disease progression in the same model ( 89 ).…”
Section: Antiepileptic Drugs (Aeds)mentioning
confidence: 99%
“…Clinically, the hypoactivity of the cholinergic system is one of the important pathological hallmarks observed in AD patients [11] . The cholinergic system is reported to play an important role in cognition and memory formation [12–14] . Further, it has been suggested that the innervations of the cholinergic neurons within hippocampus is responsible for learning and memory [15,16] and the decline in the cholinergic function is associated with cognitive deficit.…”
Section: Introductionmentioning
confidence: 99%
“…The cholinergic system in the hippocampus plays a crucial role in memory formation and cognition, and a reduction in its function is correlated with AD, resulting in cognitive impairment. Cholinergic neurons, which use the neurotransmitter acetylcholine (ACh), are within the nucleus basalis and septal diagonal band complex of the basal forebrain, and provide the main source of cholinergic innervation to the hippocampus as well as the cerebral cortex, playing a key role in attention and memory function. , …”
Section: Introductionmentioning
confidence: 99%